A prospect secondary goal model for ranking DMUs in DEA-R. (26th January 2023) - Tohidnia, Simin; Tohidi, Ghasem
This paper presents a prospect DEA-R model by combining the DEA-R model and prospect theory that can be used to evaluate DMUs in decision making under risk. In this study, the proposed model is used as a secondary goal model to determine a unique set of weights in the evaluation of DMUs by cross-efficiency method and thus the psychological behaviours of experts are incorporated in the evaluations. In fact, the present paper introduces an approach for ranking DMUs in DEA-R that can be useful in decision making under risk and especially for decision-makers who are familiar with ratio analysis. An empirical application also will be presented to illustrate the applicability of the proposed model.